2020
DOI: 10.1177/1847979020901982
|View full text |Cite
|
Sign up to set email alerts
|

Toward a model to apprehend the complexity of manufacturing firm’s overall performance

Abstract: Recently, the company’s overall performance (OP) has become a major concern of our modern society, as a key factor that can potentially increase firm’s competitive advantage and ensure its sustainable development. However, OP is increasingly being considered as highly complex because of the complex interrelationships within industrial systems. This article presents a contribution to modeling of OP in order to apprehend its complexity and take into account the interactions between all its aspects. The proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
2
8
0
Order By: Relevance
“…While Achua (2011) found that public sector organizations are unwilling to adopt online systems due to a lack of competencies and knowledge that impedes organizational performance. Conversely, knowledge enhances the performance of a novice for a particular role or job (Guo & Zhang, 2022;Lamjahdi et al, 2020;Lueck & Peek, 2012;Steensma & Groeneveld, 2010). Naidoo and Wu (2011) researched 570 inventory control experts from New Zealand, Australia, the United States, and the United Kingdom and established that the designated staff could professionally plan and control the inventory effectively if knowledge had been imparted to them.…”
Section: Knowledge and Inventory Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…While Achua (2011) found that public sector organizations are unwilling to adopt online systems due to a lack of competencies and knowledge that impedes organizational performance. Conversely, knowledge enhances the performance of a novice for a particular role or job (Guo & Zhang, 2022;Lamjahdi et al, 2020;Lueck & Peek, 2012;Steensma & Groeneveld, 2010). Naidoo and Wu (2011) researched 570 inventory control experts from New Zealand, Australia, the United States, and the United Kingdom and established that the designated staff could professionally plan and control the inventory effectively if knowledge had been imparted to them.…”
Section: Knowledge and Inventory Managementmentioning
confidence: 99%
“…While Achua (2011) found that public sector organizations are unwilling to adopt online systems due to a lack of competencies and knowledge that impedes organizational performance. Conversely, knowledge enhances the performance of a novice for a particular role or job (Guo & Zhang, 2022; Lamjahdi et al, 2020; Lueck & Peek, 2012; Steensma & Groeneveld, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A QMS consists of several interrelated and interdependent processes and procedures, thus employee involvement and capacity building are crucial to its sustainability (Lamjahdi et al, 2020; WMO, 2017a). In the Malaysian local government organizations, this barrier was most impactful.…”
Section: Literature Reviewmentioning
confidence: 99%
“…35 More generally, SMEs lack access to technologies and have little knowledge about modern accounting techniques, limiting their growth on the worldwide market. 36 However, the economic instability related to the worldwide financial crisis has incentivised SMEs to change, focusing more on manufacturing processes 36 to improve their profitability 37 and reducing idle capacity , an expense impacting the bottom line through the ABC method. In this way, managers can make all efforts to reengineer manufacturing processes, using excess capacity to minimise production costs.…”
Section: Research Questionsmentioning
confidence: 99%